2018
DOI: 10.1093/intimm/dxy061
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil-derived neurotoxin enhances airway remodeling in eosinophilic chronic rhinosinusitis and correlates with disease severity

Abstract: Eosinophilic chronic rhinosinusitis (ECRS) is a subtype of chronic rhinosinusitis (CRS) that is characterized by intractable nasal polyp formation. Eosinophil-derived neurotoxin (EDN) is an eosinophil granule protein that is closely related to allergic inflammation, but the pathological implications of EDN in ECRS remain unknown. In this study, we evaluated the function of EDN in ECRS pathogenesis and assessed its potential as a disease activity marker. Serum EDN levels were significantly higher in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 32 publications
3
44
0
1
Order By: Relevance
“…In addition, we have previously shown that eosinophil granule protein acts on nasal epithelial cells to enhance MMP-9 production. 31 Based on these findings, it is considered that epithelial cells are one of the main sources of MMP-9 in ECRS. Interestingly, the expression of membrane SEMA4D on eosinophils was downregulated in patients with ECRS, whereas downregulation of SEMA4D was not detected in other leukocytes, suggesting that the MMP-9-mediated shedding process of eosinophils is unique and specific.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have previously shown that eosinophil granule protein acts on nasal epithelial cells to enhance MMP-9 production. 31 Based on these findings, it is considered that epithelial cells are one of the main sources of MMP-9 in ECRS. Interestingly, the expression of membrane SEMA4D on eosinophils was downregulated in patients with ECRS, whereas downregulation of SEMA4D was not detected in other leukocytes, suggesting that the MMP-9-mediated shedding process of eosinophils is unique and specific.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils in response to Staphylococcus aureus, release EDN [37]. EDN induces production of MMP-9 from the nasal epithelium and involves in the pathogenesis of chronic eosinophilic rhinosinusitis [38]. Eosinophil-derived neurotoxin correlated with the disease severity of AD and considered as a serum biomarker for disease severity in atopic dermatitis [39].…”
Section: Eosinophil-derived Neurotoxin (Edn)mentioning
confidence: 99%
“…Elevated levels of EDN have been observed in asthma patients, with higher levels being measured during asthma exacerbations compared to those with stable asthma [14]. Furthermore, sustained exposure to high levels of EDN may have detrimental effects on the surrounding tissues with EDN being linked to airway remodelling in eosinophilic chronic rhinosinusitis by inducing production of matrix metalloproteinase 9 [15]. This suggests that prolonged airway exposure to elevated levels of EDN may be a risk factor for the progression of disease pathology.…”
Section: Introductionmentioning
confidence: 99%